TEACHING GERMAN WITH DIGITAL MEDIA (World Bulletin of Social Sciences, 2024)
Digital media is spreading in all areas of our lives, and education is no exception. Nowadays, there are many ways to use digital media in GFL lessons. Neither teachers nor students have the necessary digital skills. This article examines the specific characteristics of generation Z that affect the structure of the educational process, and against this background, criteria for the rational use of digital media in GFL lessons are determined.